2021
DOI: 10.1186/s13052-021-00994-w
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of a dynamically increased red blood cell distribution width in very low birth weight infants with serious bacterial infection

Abstract: Objective Serious bacterial infection (SBI) remains an important cause of morbidity and mortality in preterm infants. The objective of this study was to evaluate the dynamically increased value of the red cell distribution width (RDW) in the diagnosis of SBI. Methods This retrospective study enrolled 334 preterm infants with birth weight less than 1500 g. The initial RDW and the maximum value of RDW during hospitalization were extracted from the MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
1
5
0
1
Order By: Relevance
“…The finding is in line, as reported by Hu et al, who reported 18.9-19.9% as the diagnostic threshold for neonatal sepsis [51]. Similar other studies support our hypothesis on the diagnostic values of RDW in neonatal sepsis [52][53][54][55][56].…”
Section: Discussionsupporting
confidence: 93%
“…The finding is in line, as reported by Hu et al, who reported 18.9-19.9% as the diagnostic threshold for neonatal sepsis [51]. Similar other studies support our hypothesis on the diagnostic values of RDW in neonatal sepsis [52][53][54][55][56].…”
Section: Discussionsupporting
confidence: 93%
“…It is used either to record the difference between RDW values at baseline and at various time points after clinical treatment or name unit changes in RDW in the study population by the investigator. ΔRDW has aroused the attention of some researchers in predicting the risk of infection in particular people, 4 early postoperative morbidity, 5 disease survival outcomes, 6 , 7 and risk stratification of patients. 8 …”
Section: Introductionmentioning
confidence: 99%
“…The literature data on RDW and its clinical relevance in newborns are scarce, but there are studies showing that high RDW values may be an early prognostic biomarker for outcomes in neonatal sepsis, transient tachypnea of the newborn, critically ill children, and critical pediatric diseases such as severe bacterial infection. 4 , 5 , 6 , 7 , 8 RDW assessment has an important role in determining the severity and prognosis of cardiac autonomic dysfunction and cardiovascular disease in adults. 9 , 10 A number of diseases that are characterized by inflammatory burden are associated with elevated RDW levels, such as autoimmune, 11 gastrointestinal 12 and liver 13 diseases, and malignancy conditions.…”
Section: Introductionmentioning
confidence: 99%